New findings and complete recording for three turtles of conservation interest in the Bolivian chaco - Cabrera, Mario Roberto (2024)
All records gathered since 1997 for the turtles Acanthochelys pallidipectoris (8 localities), Chelonoidis chilensis (6) and Kinosternon s. scorpioides (14), in the Chaco ecoregion of Tarija Department, Bolivia, are presented georeferenced and mapped. These data contribute to precise and expand the geographic range of these three taxa in a region affected by anthropogenic alteration sustained over time.